Weather-resistant artificial turf fiber based on high-performance polypropylene and process for the production thereof
Patent Information
- Application Number
- CN202611170585.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-09-22
AI Technical Summary
[0005]本发明克服了现有技术的不足,提供一种高性能聚丙烯及基于该高性能聚丙烯的耐候型人造草坪纤维制备工艺,以解决现有聚丙烯人造草坪纤维采用全截面均匀复配时,不同改性组分和结构要求相互牵制,难以同时获得稳定的熔融加工性能、较高的表层取向承载能力、有效的表层耐候保护以及对纵向微裂纹扩展抑制能力的问题
[0030](1)本发明在180-220℃下完成30-120s的支化反应并经15-60s真空脱挥后,再加入稳定-成核母粒。该时序使抗氧剂不进入主要自由基反应阶段,降低稳定剂对自由基支化的抑制;纳米成核剂进入熔体后的混合停留时间控制为15-45s,减少其在高温和剪切作用下的二次团聚。所得高性能聚丙烯的凝胶质量分数不高于0.50%,同时具有10-25cN的F30熔体强度和可恢复取向应变。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of high-performance polypropylene technology, and in particular to a weather-resistant artificial turf fiber based on high-performance polypropylene and its preparation process. Background Technology
[0002] Artificial turf fibers are exposed to sunlight, oxygen, temperature fluctuations, and repeated trampling over long periods. Their surface is subjected to ultraviolet radiation and thermo-oxidative aging, as well as bending, friction, and localized stretching. Polypropylene, with its low density, good chemical resistance, ease of melt processing, and moderate cost, can be used to produce monofilaments or ribbon fibers for artificial turf. However, polypropylene molecular chains are prone to breakage under the combined effects of light, heat, and oxygen. Tiny defects on the surface of oriented fibers can also propagate along the fiber length under cyclic loading, resulting in surface embrittlement, longitudinal branching, fibrillation, and breakage.
[0003] Existing methods typically involve directly adding antioxidants, hindered amine light stabilizers, UV absorbers, inorganic fillers, nucleating agents, or branching modifiers to polypropylene and uniformly dispersing them during the same melt processing. While these methods can improve weather resistance, crystallization behavior, or melt stability individually, it is difficult to coordinate different modification objectives: the free radical branching reaction may be affected by the stabilizer capturing free radicals, and increased branching may weaken the regular orientation and wear resistance of the fiber surface; inorganic nano-components may also agglomerate after prolonged high-temperature and high-shear conditions, forming localized stress concentrations on the surface of highly oriented filaments. Therefore, relying solely on uniform compounding across the entire cross-section makes it difficult to simultaneously achieve melt processing stability, surface weather resistance, surface orientation strength, and long-term anti-branching properties.
[0004] Therefore, it is necessary to provide a weather-resistant artificial turf fiber based on high-performance polypropylene and its preparation process to solve the above problems. Summary of the Invention
[0005] This invention overcomes the shortcomings of the prior art and provides a high-performance polypropylene and a preparation process for weather-resistant artificial turf fiber based on the high-performance polypropylene. This solves the problem that when existing polypropylene artificial turf fibers are uniformly compounded across the entire cross section, different modified components and structural requirements restrain each other, making it difficult to simultaneously obtain stable melt processing performance, high surface orientation load-bearing capacity, effective surface weather protection, and the ability to inhibit the propagation of longitudinal microcracks.
[0006] To achieve the above objectives, the present invention adopts the following technical solution.
[0007] In a first aspect, a method for preparing high-performance polypropylene includes the following steps:
[0008] S1. Based on 100 parts by weight of isotactic polypropylene, mix 0.01-0.08 parts by weight of free radical initiator and 0.05-0.50 parts by weight of multifunctional branching agent to obtain the reactant.
[0009] S2. The reactants are melted and reacted at 180-220°C for 30-120 seconds to form sparse long-chain branched polypropylene.
[0010] S3. Vacuum devolatilization for 15-60 seconds at a gauge pressure of -0.06 to -0.095 MPa;
[0011] S4. Add 0.5-3.0 parts by weight of stabilizing-nucleating masterbatch to the melt after vacuum devouring. The stabilizing-nucleating masterbatch contains processing antioxidant, auxiliary antioxidant and surface-treated nano-nucleating agent.
[0012] S5, mix, extrude and granulate to obtain high-performance polypropylene.
[0013] In a preferred embodiment of the present invention, the free radical initiator is one of dicumyl peroxide, 2,5-dimethyl-2,5-di-tert-butylperoxyhexane, or benzoyl peroxide;
[0014] The multifunctional branching agent is one of trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, or triallyl isocyanurate.
[0015] In a preferred embodiment of the present invention, the isotactic polypropylene has a melt mass flow rate of 2.0-8.0 g / 10 min at 230°C and 2.16 kg, and an isotactic index of not less than 96.0%.
[0016] In a preferred embodiment of the present invention, the stabilized nucleating masterbatch comprises, by mass percentage, 70-88% polypropylene carrier, 4-10% processing antioxidant, 4-10% auxiliary antioxidant, and 4-12% surface-treated nano-nucleating agent, with the sum of the contents of each component being 100%, and the D50 particle size of the nano-nucleating agent being 30-100 nm.
[0017] Secondly, a high-performance polypropylene prepared by the aforementioned preparation method.
[0018] Thirdly, a preparation process for weather-resistant artificial turf fiber based on high-performance polypropylene includes the following steps:
[0019] S1. Using the high-performance polypropylene as the core layer material, and isotactic polypropylene and weather-resistant masterbatch with no free radical branching treatment and a gel mass fraction of no more than 0.10% as the skin layer material.
[0020] S2. Prepare single-layer standard samples from the core layer raw material and the skin layer raw material at the same main drawing temperature, main drawing ratio, supplementary drawing temperature and supplementary drawing ratio as the composite grass fiber, and determine the free heat shrinkage rate at 115-145℃.
[0021] S3. Co-extrude the core layer material and the sheath layer material into a composite primary grass fiber with the sheath layer continuously covering the core layer.
[0022] S4. Perform main stretching and supplementary stretching on the composite primary grass fibers in sequence;
[0023] S5. Implement controlled shrinkage at 115-145℃, so that the actual shrinkage rate is greater than the free thermal shrinkage rate of the skin material and less than the free thermal shrinkage rate of the core material.
[0024] S6. Under constant length or tension of 0.02-0.12 cN / dtex, cool to below 40°C within 2-8 seconds.
[0025] In a preferred embodiment of the present invention, the core layer accounts for 55-80% of the total mass of the composite primary grass fibers, the skin layer accounts for 20-45%, and the offset of the geometric center of the core layer cross section relative to the geometric center of the composite primary grass fiber cross section is no greater than 5% of the equivalent radius of the composite primary grass fibers.
[0026] In a preferred embodiment of the present invention, the weather-resistant masterbatch comprises, by mass percentage, 45-65% polypropylene carrier, 4-10% primary antioxidant, 4-10% secondary antioxidant, 10-20% hindered amine light stabilizer, 4-10% ultraviolet absorber, and 10-25% pigment, with the sum of the contents of each component being 100%, and the mass fraction of the weather-resistant masterbatch in the skin layer raw material is 3-8%.
[0027] In a preferred embodiment of the present invention, the temperature of the main stretching is 70-105℃ and the stretching ratio is 3.2-4.8 times, and the temperature of the supplementary stretching is 115-145℃ and the stretching ratio is 1.05-1.25 times.
[0028] In a preferred embodiment of the present invention, the difference in free thermal shrinkage rate between the core material and the skin material is 2.0%-7.0%, and the actual shrinkage rate is 0.5%-4.0% higher than the free thermal shrinkage rate of the skin material and 0.5%-4% lower than the free thermal shrinkage rate of the core material.
[0029] This invention addresses the shortcomings of the prior art and has the following beneficial effects:
[0030] (1) In this invention, a branching reaction is completed at 180-220℃ for 30-120s, followed by vacuum devolatilization for 15-60s, and then a stabilizing-nucleating masterbatch is added. This timing prevents the antioxidant from entering the main free radical reaction stage, reducing the inhibitory effect of the stabilizer on free radical branching; the mixing residence time of the nano-nucleating agent after entering the melt is controlled at 15-45s, reducing its secondary agglomeration under high temperature and shear. The resulting high-performance polypropylene has a gel mass fraction of no more than 0.50%, and simultaneously possesses an F30 melt strength of 10-25cN and recoverable orientation strain.
[0031] (2) This invention employs a homogeneous polypropylene core-sheath composite structure, with a sparse long-chain branched structure and a refined crystalline structure set in the core layer, and isotactic polypropylene with a gel mass fraction of no more than 0.10% and a weather-resistant system set in the sheath layer without free radical branching treatment. The core layer provides melt stability, bending support, and shrinkage driving force, while the sheath layer provides surface bearing capacity, wear resistance, and weather protection, avoiding the reduction of surface orientation due to the use of branched polypropylene throughout the grass fibers.
[0032] (3) In this invention, the offset of the geometric center of the core layer cross section relative to the geometric center of the grass fiber cross section is controlled to within 5% of the equivalent radius, and the actual shrinkage rate is 0.5%-4.0% higher than the free thermal shrinkage rate of the skin layer and 0.5%-4.0% lower than the free thermal shrinkage rate of the core layer. After shrinkage and cooling, the skin layer forms axial residual compressive stress, and the core layer forms axial residual tensile stress to balance it. Moreover, the shrinkage mismatch will not form an eccentric bending moment sufficient to cause the grass fiber to continuously bend or spirally deform.
[0033] (4) The primary antioxidant, secondary antioxidant, hindered amine light stabilizer, and UV absorber in the cortex reduce the photo-oxidation rate of the polypropylene surface, and the residual compressive stress in the cortex reduces the opening displacement of surface microcracks during bending, trampling, and thermo-oxidative aging. The former delays crack initiation, while the latter inhibits crack opening and propagation along the orientation direction, thereby reducing longitudinal bifurcation, fibrillation, and breakage after combined UV irradiation and mechanical wear. Detailed Implementation
[0034] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, other embodiments obtained by those of ordinary skill in the art without creative effort are all within the scope of protection of the present invention.
[0035] The following description provides specific raw material manufacturers, trade names, compositions, process parameters, and test values. Unless otherwise stated, all percentages by mass are based on the total mass of the corresponding mixture, and all parts by mass are based on 100 parts of the polypropylene matrix in the corresponding step.
[0036] The isotactic polypropylene A used in the following examples was purchased from Zhenhai Refining & Chemical Co., Ltd. of China Petroleum & Chemical Corporation, with the grade PPH-T03 (T30S). Its melt flow rate at 230℃ and 2.16 kg was measured to be 3.2 g / 10 min, and its isotactic index was 97.4%. Isotactic polypropylene B was purchased from Qilu Branch of China Petroleum & Chemical Corporation, with the grade T36F. Its melt flow rate at 230℃ and 2.16 kg was measured to be 4.1 g / 10 min, its isotactic index was 97.8%, and its gel mass fraction was 0.04%. Dicumyl peroxide was purchased from Hefei Anbang Chemical Co., Ltd., with the product name DCP and a purity of 99.1% upon arrival. Trimethylolpropane trimethacrylate was purchased from Hefei Anbang Chemical Co., Ltd., with the trade name JN851. The main antioxidant was purchased from Tianjin Lianlong New Materials Co., Ltd., with the grade RIANOX. 1010; The auxiliary antioxidant was purchased from Tianjin Lianlong New Material Co., Ltd., brand name RIANOX 168; the hindered amine light stabilizer was purchased from Tianjin Lianlong New Material Co., Ltd., brand name RIASORB UV-944, with a number average molecular weight of 2000-3100; the ultraviolet absorber was purchased from Tianjin Lianlong New Material Co., Ltd., brand name RIASORB UV-326; the nano calcium carbonate was purchased from Guangxi Huana New Material Technology Co., Ltd., brand name CCS-18, with stearic acid as the surface treatment agent, and its D50 particle size was measured to be 84nm, D90 particle size to be 136nm, and moisture content to be 0.24%; the phthalocyanine green pigment was purchased from Baihehua Group Co., Ltd., brand name phthalocyanine green 311, color index number CIPG7.
[0037] The stabilized nucleation masterbatch was prepared by the following method: isotactic polypropylene B and nano-calcium carbonate were dried at 80℃ for 2 h; 82 parts of isotactic polypropylene B, 6 parts of RIANOX 1010, 6 parts of RIANOX 168 and 6 parts of CCS-18 nano-calcium carbonate were weighed and mixed at 600 r / min for 6 min; the mixture was continuously added to the twin-screw extruder melting and mixing section, with the temperatures of each zone set to 170℃, 180℃, 190℃, 195℃, 195℃ and 190℃ respectively, the screw speed was 220 r / min, the feed rate was 8.0 kg / h, and the vacuum port gauge pressure was -0.080 MPa; after water cooling and pelletizing, the melt was dried at 80℃ for 2 h to obtain the stabilized nucleation masterbatch.
[0038] Weather-resistant masterbatch was prepared by the following method: 55 parts of isotactic polypropylene B, 6 parts of RIANOX1010, 6 parts of RIANOX168, 14 parts of RIASORB UV-944, 6 parts of RIASORB UV-326, and 13 parts of phthalocyanine green 311 were weighed and mixed at 600 r / min for 8 min; the mixture was continuously added to the twin-screw extruder melt mixing section, with the temperatures of each zone set sequentially to 165℃, 175℃, 185℃, 190℃, 190℃, and 185℃, the screw speed being 200 r / min, the feed rate being 8.0 kg / h, and the vacuum port gauge pressure being -0.075 MPa; after water cooling and pelletizing, the melt was dried at 75℃ for 2 h to obtain the weather-resistant masterbatch.
[0039] This invention provides a method for preparing high-performance polypropylene, comprising the following steps:
[0040] S1. Based on 100 parts by weight of isotactic polypropylene, mix 0.01-0.08 parts by weight of free radical initiator and 0.05-0.50 parts by weight of multifunctional branching agent to obtain the reactant.
[0041] S2. The reactants are melted and reacted at 180-220°C for 30-120 seconds to form sparse long-chain branched polypropylene.
[0042] S3. Vacuum devolatilization for 15-60 seconds at a gauge pressure of -0.06 to -0.095 MPa;
[0043] S4. Add 0.5-3.0 parts by mass of stabilizing-nucleating masterbatch to the melt after vacuum devouring, so that the mixing residence time of the stabilizing-nucleating masterbatch in the melt is 15-45s;
[0044] S5. Extrusion and granulation yield high-performance polypropylene.
[0045] Step S1 involves the preparation of the reactants. First, the free radical initiator is diluted with 1.0-3.0% of the total isotactic polypropylene particles. Then, it is mixed with the remaining polypropylene and the multifunctional branching agent for 5-12 minutes to ensure the free radical initiator and multifunctional branching agent are evenly distributed on the surface of the polypropylene particles, reducing excessive chain scission and localized gelation of polypropylene caused by excessively high local peroxide concentrations.
[0046] Step S2 is the melt branching reaction of polypropylene. The reactants melt at 180-220℃ for 30-120s. The free radical initiator decomposes and causes the polypropylene segments to form macromolecular free radicals. Multifunctional branching agents participate in free radical addition and interchain linkage to form a sparse long-chain branched structure that can improve the tensile load of the melt and has a gel mass fraction of no more than 0.50%.
[0047] Step S3 is vacuum devolatilization after the branching reaction. A vacuum of -0.06 to -0.095 MPa is applied to the polypropylene melt after the 30-120s branching reaction and maintained for 15-60s to remove unreacted low-molecular-weight branching agents, initiator decomposition products, and volatile substances. Processing antioxidants and auxiliary antioxidants are added after this step and do not enter the aforementioned free radical branching zone.
[0048] Step S4 involves the downstream addition of the stabilizing-nucleating masterbatch. The melt residence time from the addition of the stabilizing-nucleating masterbatch to the extruder is controlled to be 15-45 s, which allows RIANOX 1010 and RIANOX 168 to suppress oxidation and uncontrolled chain scission in the subsequent thermal history, and to ensure that CCS-18 nano-calcium carbonate is fully dispersed without undergoing the free radical reaction and high-temperature shear in the first 30-120 s.
[0049] Step S5 is extrusion granulation. The melt after adding the stabilizing-nucleating masterbatch is dispersed and mixed, extruded, water-cooled and pelletized to obtain high-performance polypropylene with a melt mass flow rate of 1.0-5.0 g / 10 min, an F30 melt strength of 10-25 cN and a gel mass fraction of no more than 0.50% under the conditions of 230℃ and 2.16 kg.
[0050] This invention also provides a method for preparing weather-resistant artificial turf fiber based on the above-mentioned high-performance polypropylene, comprising the following steps:
[0051] S1. Using the above-mentioned high-performance polypropylene as the core layer material, and isotactic polypropylene and weather-resistant masterbatch with no free radical branching treatment and a gel mass fraction of no more than 0.10% as the skin layer material.
[0052] S2. Prepare single-layer standard samples from the core layer raw material and the skin layer raw material at the same main drawing temperature, main drawing ratio, supplementary drawing temperature and supplementary drawing ratio as the composite grass fiber, and determine the free heat shrinkage rate at 115-145℃.
[0053] S3. Co-extrude the core layer material and the sheath layer material into a composite primary grass fiber with the sheath layer continuously covering the core layer.
[0054] S4. Perform main stretching and supplementary stretching on the composite primary grass fibers in sequence;
[0055] S5. Implement controlled shrinkage at 115-145℃, so that the actual shrinkage rate is greater than the free thermal shrinkage rate of the skin material and less than the free thermal shrinkage rate of the core material.
[0056] S6. Under constant length or tension of 0.02-0.12 cN / dtex, cool to below 40°C within 2-8 seconds.
[0057] Step S1 involves the preparation of the core and sheath materials. The core layer uses the aforementioned high-performance polypropylene; the sheath layer uses isotactic polypropylene B, with 3-8% of weather-resistant masterbatch added to the total mass of the sheath material. The isotactic polypropylene in the sheath layer that has not undergone free radical branching treatment maintains a gel mass fraction of no more than 0.10%, and the RIANOX 1010, RIANOX 168, RIASORB UV-944, and RIASORB UV-326 in the weather-resistant masterbatch are concentrated on the fiber surface.
[0058] Step S2 is the determination of free heat shrinkage rate. Single-layer standard samples were prepared using core layer and sheath materials, respectively. Both standard samples and the composite straw were subjected to the same extrusion temperature, main draw temperature, main draw ratio, supplementary draw temperature, supplementary draw ratio, and residence time in each temperature zone. Samples with a gauge length of 200.0 mm were treated without axial constraint at 115-145℃ for 5 min. The free heat shrinkage rate was calculated as the percentage difference between the gauge length before and after treatment relative to the gauge length before treatment.
[0059] Step S3 involves homogeneous polypropylene core-sheath composite molding. The core layer raw material and the sheath layer raw material are separately melted, metered, and then co-extruded to form a composite nascent grass fiber with the sheath continuously covering the core layer. The core layer accounts for 55-80% of the total mass of the composite nascent grass fiber, and the sheath layer accounts for 20-45%. The offset of the geometric center of the core layer cross-section relative to the geometric center of the grass fiber cross-section is controlled to be within 5% of the equivalent radius of the grass fiber.
[0060] Step S4 involves a two-stage drawing process. The composite primary grass fibers are first subjected to a main drawing of 3.2-4.8 times at 70-105℃, followed by a supplementary drawing of 1.05-1.25 times at 115-145℃. The supplementary drawing temperature is higher than the main drawing temperature, and the supplementary drawing ratio is lower than the main drawing ratio, in order to perfect the orientation of the cortex crystals and preserve the recoverable orientation strain of the core layer.
[0061] Step S5 is controlled shrinkage. The linear speed of the guide rollers before and after the shrinkage zone is adjusted at 115-145℃ so that the actual shrinkage rate is 0.5%-4.0% higher than the free thermal shrinkage rate of the outer layer material and 0.5%-4.0% lower than the free thermal shrinkage rate of the core layer material. The actual shortening of the outer layer is greater than its free shrinkage, and the actual shortening of the core layer is less than its free shrinkage.
[0062] Step S6 is cooling and shaping. After controlled retraction, the grass fibers are kept at a constant length, or the axial tension of the grass fibers is controlled to 0.02-0.12 cN / dtex, and the temperature of the grass fibers is reduced to below 40°C within 2-8 seconds. After cooling, residual compressive stress is formed in the skin layer along the length of the grass fibers, and residual tensile stress is formed in the core layer to balance the compressive stress in the skin layer.
[0063] Example 1:
[0064] This embodiment needs to address the following specific difficulties simultaneously: the branching reaction needs to form a long-chain branched structure in the core polypropylene that can improve melt strength and free heat shrinkage, but the gel mass fraction must not exceed 0.50%; RIANOX 1010, RIANOX 168 and CCS-18 nano calcium carbonate need to enter the core polypropylene, but cannot stay in the free radical branching region; the skin layer needs to maintain a highly oriented polypropylene surface with a gel mass fraction not higher than 0.10%, and RIASORB UV-944 and RIASORB UV-326 should be centrally configured; the actual shrinkage rate needs to be higher than the skin layer free heat shrinkage rate and lower than the core layer free heat shrinkage rate.
[0065] Weigh out 100 parts of isotactic polypropylene A, 0.035 parts of DCP, and 0.22 parts of JN851 trimethylolpropane trimethacrylate. First, mix DCP with 2 parts of isotactic polypropylene A at 600 r / min for 3 min to form a diluent. Then add the remaining isotactic polypropylene A and JN851, and continue mixing at 600 r / min for 8 min to obtain the reactant.
[0066] The reactants were continuously fed into the twin-screw reactive extruder at a rate of 10.0 kg / h, with a screw speed of 180 r / min. The temperatures in the front section were 185℃, 195℃, 205℃, and 208℃, respectively, and the residence time of the melt within the 180-220℃ range was 68 s. After leaving the branching reaction zone, the melt underwent vacuum devolatilization for 32 s at a gauge pressure of -0.088 MPa.
[0067] After vacuum devolatilization, 1.8 parts of stabilized-nucleating masterbatch were added from the downstream feed port. The melt residence time from the side feed port to the die was 24 s, and the downstream mixing temperature was 202 °C. The melt was extruded, water-cooled at 25 °C, and pelletized to obtain the high-performance polypropylene of Example 1. The obtained pellets were dried at 80 °C for 2 h. The melt mass flow rate of this high-performance polypropylene at 230 °C and 2.16 kg was 2.36 g / 10 min.
[0068] 94 parts of isotactic polypropylene and 6 parts of weather-resistant masterbatch were weighed and mixed at 500 r / min for 10 min to obtain the skin layer raw material. Based on the total mass of the skin layer raw material, the mass fractions of RIANOX 1010, RIANOX 168, RIASORB UV-944, RIASORB UV-326, and Phthalocyanine Green 311 were 0.36%, 0.36%, 0.84%, 0.36%, and 0.78%, respectively.
[0069] The high-performance polypropylene and sheath material from Example 1 were extruded into single-layer flat nascent filaments at 210°C. Both types of single-layer nascent filaments underwent a 4-fold main draw at 92°C, followed by a 1.12-fold supplementary draw at 132°C, for a total draw ratio of 4.48. The residence times in the main draw zone and the supplementary draw zone were 12.0 s and 9.5 s, respectively. After drawing, the filaments were equilibrated for 24 h at 23°C and 50% relative humidity.
[0070] Ten specimens with a gauge length of 200.0 mm were cut from each type of monolayer sample and treated at 132°C for 5 min without axial tension. After removal, they were cooled to 23°C without constraint. The free thermal shrinkage rate was calculated as the percentage difference between the gauge length before and after treatment relative to the gauge length before treatment. The measured free thermal shrinkage rate of the core material was 8.6%, and that of the skin material was 4.2%.
[0071] The dried high-performance polypropylene is fed into the core melt channel, and the skin material is fed into the skin melt channel. The melt temperatures of the core and skin are 210℃ and 208℃, respectively. The two melts are merged through a centrally symmetrical distribution channel and co-extruded through a flat composite die. The mixture is then cooled in a 28℃ water bath to obtain composite nascent grass filaments with a continuously coated skin. The mass ratio of core to skin is 68.0:32.0. The average width of the composite nascent grass filaments is 1.26 mm, and the average thickness is 0.176 mm.
[0072] The composite nascent grass fibers were subjected to a 4.00-fold main draft at 92℃, with a residence time of 12.0 s in the main drafting zone; subsequently, a 1.12-fold supplementary draft was performed at 132℃, with a residence time of 9.5 s in the supplementary drafting zone. During the drafting process, the linear velocity fluctuation of the grass fibers did not exceed 0.4% of the set value, and the drafted grass fibers did not exhibit necking, discontinuity, surface adhesion, or delamination of the core and sheath.
[0073] The drawn composite straw fibers are introduced into the 132°C shrinkage zone. By adjusting the linear speeds of the inlet and outlet guide rollers, the actual shrinkage rate is made to be 6.3%. The actual shrinkage rate is calculated as the percentage of the difference between the inlet and outlet linear speeds relative to the inlet linear speed. The actual shrinkage rate is higher than the 4.2% free heat shrinkage rate of the outer layer material (2.1%) and lower than the 8.6% free heat shrinkage rate of the core layer material (2.3%).
[0074] After controlled retraction, the grass fibers were introduced into a 25°C cooling zone with an axial tension of 0.052 cN / dtex, reducing the grass fiber temperature to 38°C within 3.6 seconds. The fibers were then wound to obtain the weather-resistant artificial turf fiber of Example 1. This fiber has an average width of 1.19 mm and an average thickness of 0.168 mm. After continuous winding for 1000 m, the lateral displacement of the grass fibers did not exceed 2.4 mm, and no helical deformation or delamination at the core-sheath interface was observed.
[0075] Example 2:
[0076] The only difference between this embodiment and Example 1 is that, when preparing high-performance polypropylene, the amount of JN851 trimethylolpropane trimethacrylate added is adjusted from 0.220 parts to 0.050 parts; the amount of dicumyl peroxide added, the branching reaction temperature and time, the vacuum devolatilization conditions, the amount and location of the stable-nucleation masterbatch added, the composition of the skin material, the skin-core mass ratio, and the main and supplementary drawing conditions are all the same as in Example 1.
[0077] Single-layer standard samples were prepared using the same stretching heat history as in Example 1. After treatment at 132°C without axial constraint for 5 minutes, the free heat shrinkage rate of the core material was measured to be 6.9%, while the free heat shrinkage rate of the sheath material remained at 4.2%. The actual shrinkage rate of the composite grass fibers was controlled at 6.3%, which was 2.1% higher than the free heat shrinkage rate of the sheath material and 0.6% lower than the free heat shrinkage rate of the core material. The remaining steps and process parameters were completely consistent with those in Example 1.
[0078] Example 3:
[0079] The only difference between this embodiment and Example 1 is that the amount of JN851 trimethylolpropane trimethacrylate added is adjusted from 0.220 parts to 0.500 parts when preparing high-performance polypropylene; the other raw material amounts, branching reaction, vacuum devolatilization, downstream addition of stabilizing-nucleating masterbatch, core-sheath co-extrusion, two-stage stretching and cooling and shaping conditions are the same as in Example 1.
[0080] Single-layer standard samples were prepared using the same stretching heat history as in Example 1. After treatment at 132°C without axial constraint for 5 minutes, the free heat shrinkage rate of the core material was measured to be 10.2%, and the free heat shrinkage rate of the sheath material was 4.2%. The actual shrinkage rate of the composite grass fibers was still 6.3%, higher than the free heat shrinkage rate of the sheath material (2.1%), but lower than the free heat shrinkage rate of the core material (3.9%). The remaining steps and process parameters were completely consistent with Example 1.
[0081] Example 4:
[0082] The only difference between this embodiment and Example 1 is that the actual shrinkage rate in the 132°C shrinkage zone is adjusted from 6.3% to 4.7%. This actual shrinkage rate is 0.5% higher than the 4.2% free heat shrinkage rate of the skin layer material and 3.9% lower than the 8.6% free heat shrinkage rate of the core layer material. The preparation of the high-performance polypropylene core layer, the composition of the skin layer material, the skin-to-core mass ratio, the co-extrusion temperature, the main drawing and supplementary drawing conditions, and the cooling conditions are all the same as in Example 1.
[0083] Example 5:
[0084] The only difference between this embodiment and Example 1 is that the actual shrinkage rate was adjusted from 6.3% to 8.1% within the 132°C shrinkage zone. This actual shrinkage rate is higher than the 4.2% free heat shrinkage rate of the skin layer material (3.9%) and lower than the 8.6% free heat shrinkage rate of the core layer material (0.5%). The preparation of the high-performance polypropylene core layer, the composition of the skin layer material, the skin-to-core mass ratio, the co-extrusion temperature, the main and supplementary drawing conditions, and the cooling conditions are all the same as in Example 1.
[0085] Comparative Example 1:
[0086] The only difference between this comparative example and Example 1 is the order in which the stabilizing-nucleating masterbatch is added. 100 parts of isotactic polypropylene A, 0.035 parts of DCP, 0.220 parts of JN851 trimethylolpropane trimethacrylate, and 1.8 parts of the stabilizing-nucleating masterbatch are mixed together at 600 rpm for 8 minutes, and then the resulting mixture is added to the twin-screw reactive extrusion section. No further stabilizing-nucleating masterbatch is added to the downstream feed port after vacuum devolatilization. The branching reaction zone temperature, 68-s residence time, -0.088 MPa vacuum devolatilization conditions, skin material, skin-core co-extrusion, two-stage drawing, 6.3% actual shrinkage rate, and cooling and setting conditions are all the same as in Example 1.
[0087] Single-layer standard samples were prepared using the same stretching heat history as in Example 1. The free heat shrinkage rate of the core material in this comparative example at 132°C was measured to be 5.5%, which is lower than the actual shrinkage rate of 6.3%; the free heat shrinkage rate of the skin material was still 4.2%.
[0088] Comparative Example 2:
[0089] The only difference between this comparative example and Example 1 is the elimination of the core-sheath cross-section spatial separation structure. 68.0 parts of the high-performance polypropylene obtained in Example 1 were mixed with 32.0 parts of the sheath material from Example 1 for 10 minutes to obtain a homogeneous raw material with the same total raw material composition as the composite grass fibers of Example 1. Extrusion was performed using a single-layer flat die at 209°C, and the same 28°C water bath cooling, 4.00 times main draw, 1.12 times supplementary draw, 6.3% actual shrinkage rate, and low-tension cooling conditions as in Example 1 were applied.
[0090] Homogeneous single-layer standard specimens were prepared using the same stretching thermal history as grass fibers. After treatment at 132℃ without axial constraint for 5 min, the free thermal shrinkage rate of the homogeneous material was measured to be 6.7%. This comparative example does not have a continuous skin and core layer, nor does it have an independent shrinkage window between the skin free thermal shrinkage rate and the core free thermal shrinkage rate.
[0091] Comparative Example 3:
[0092] The only difference between this comparative example and Example 1 is that the actual shrinkage rate in the 132°C shrinkage zone was adjusted from 6.3% to 3.7%, which is 0.5% lower than the 4.2% free thermal shrinkage rate of the skin material and 4.9% lower than the 8.6% free thermal shrinkage rate of the core material. All other materials, skin-core structure, stretching thermal history, and cooling conditions are the same as in Example 1.
[0093] Comparative Example 4:
[0094] The only difference between this comparative example and Example 1 is that the actual shrinkage rate in the 132°C shrinkage zone was adjusted from 6.3% to 9.1%, which is higher than the 4.2% free thermal shrinkage rate of the skin material (4.9%) and higher than the 8.6% free thermal shrinkage rate of the core material (0.5%). All other materials, skin-core structure, stretching thermal history, and cooling conditions are the same as in Example 1.
[0095] High-performance polypropylene particles, single-layer standard samples, and artificial turf fibers were obtained according to the preparation processes of Examples 1-5 and Comparative Examples 1-4.
[0096] To avoid the influence of initial transition material and residual material before shutdown on test results during continuous production, high-performance polypropylene granules were sampled starting 10 minutes after extrusion stabilization. Samples were then taken three times every 10 minutes over the next 30 minutes. Equal masses of the three samples were mixed and used for melt tensile, gel, and agglomeration size tests. Finished straw filaments were sampled at equal intervals from the 200-800m section after continuous winding of 1000m, with no fewer than five sampling points per group. The straw filaments obtained from each sampling point were randomly assigned to tests for free heat shrinkage, microcracks, warpage, photo-oxidation, and combined abrasion to eliminate systematic biases caused by winding position.
[0097] Artificial turf samples used for combined UV irradiation and mechanical abrasion were continuously prepared using the same tufting equipment. Five samples with an effective size of 300 mm × 300 mm were prepared for each example or comparative example. The grass height deviation of each sample was controlled within ±0.8 mm, the grass fiber surface mass deviation within ±2.0%, and the filling amount deviation of quartz sand and thermoplastic elastomer particles within ±0.3 kg / m², respectively. 2 and ±0.2kg / m 2 Within. Before combined exposure, the samples were equilibrated for 48 hours at 23°C and 50% relative humidity, and their mounting positions on the rotating drum were determined by random numbering.
[0098] The performance test will now be conducted.
[0099] The testing items in this application focus on reaction timing, sparse long-chain branching, short-range dispersion of nanonucleating agents, core-skin shrinkage mismatch, and surface crack propagation. Conventional hardness, density, or color difference, which are not directly related to the invention, are not used as the main evaluation items. All samples were equilibrated for 24 hours at 23°C and 50% relative humidity before testing.
[0100] (1) Melt tensile response test. High-performance polypropylene granules were dried at 80℃ for 2 hours, and the melt tensile response was measured using a melt tensile testing device. The barrel temperature was set to 190℃, the capillary die diameter was 2.0 mm, the length-to-diameter ratio was 20, and the piston volumetric flow rate was 10.0 mm³ / h. 3 / s, the distance from the die outlet to the traction wheel is 100mm, and the linear velocity of the traction wheel is 12mm / s. 2 The acceleration increases. Record the melt tensile force when the linear velocity of the traction wheel reaches 30 mm / s, and denote it as the F30 melt strength. Perform 5 tests per group and take the average value.
[0101] The strain hardening factor was determined using a tensile fixture on a rotational rheometer. The test temperature was 190℃, and the constant Henkel strain rate was 1.0 s⁻¹. -1 The transient tensile viscosity at a Henki strain of 3.0 was recorded. Simultaneously, small-amplitude frequency scans were performed at the same temperature, and linear viscoelastic predictions were obtained based on the time-frequency correlation. The ratio of the transient tensile viscosity to the linear viscoelastic prediction was denoted as the strain hardening factor. Each test was performed three times, and the average value was taken. The F30 melt strength and strain hardening factor were used to directly characterize the tensile load-bearing capacity and nonlinear hardening ability of branched polypropylene during melt stretching.
[0102] (2) Gel mass fraction test. Weigh 0.5000 g of polypropylene particles and place them in a pre-weighed metal filter bag with a pore size of 25 μm. Reflux extract in xylene at 140 °C for 8 h. After removing the filter bag, wash it successively with xylene at 80 °C and anhydrous ethanol, and dry it at 105 °C until the difference between two consecutive weighings does not exceed 0.0002 g. The percentage of the mass of insoluble matter after extraction relative to the mass of the sample before extraction is taken as the gel mass fraction. Three parallel tests are performed for each group. This indicator is used to determine whether the free radical reaction has changed from sparse long-chain branching to obvious cross-linking or local gelation.
[0103] (3) Nanonucleating agent agglomeration size test. Polypropylene particles were brittlely fractured in liquid nitrogen, and the fracture surface was sputtered with gold for 60 s. The fracture surface was observed using a scanning electron microscope at an accelerating voltage of 10 kV and a magnification of 5000x. Combined with energy dispersive spectroscopy to confirm the calcium-rich region, 10 fields of view were randomly selected from each group of samples, each with an area of 120 μm × 90 μm. The identifiable secondary agglomerates of nano-calcium carbonate were counted using the equivalent circle diameter. The sizes of no less than 300 agglomerates were summarized, and the equivalent diameter D90 when the cumulative distribution reached 90% was calculated. This index directly reflects whether the nanonucleating agent has undergone secondary agglomeration due to entering the high-temperature and high-shear zone in the early stage.
[0104] (4) Shrinkage morphology and microcrack opening test. The free thermal shrinkage rate was determined according to the method described in Example 1. The finished grass fibers were cut into 200.0 mm long samples and laid flat at 23°C without external force for 24 h. The maximum height of the sample relative to the horizontal glass plate was measured as the warpage height. 20 grass fibers were measured in each group.
[0105] Using a diamond scribing needle with a tip radius no greater than 5 μm, pre-fabricated microcracks with a length of 2.0 mm and a depth of 25 ± 3 μm were prepared on the surface of the grass fiber cortex along the length of the grass fiber. The sample was bent 180° repeatedly around a 10.0 mm diameter cylinder at a frequency of 1.0 Hz for a total of 5000 times. After bending, an axial strain of 1.0% was applied to a 100.0 mm gauge length, and the opening displacement of the pre-fabricated microcrack at the midpoint was measured under a 200x digital microscope. Ten grass fibers were tested in each group, and the average value was taken. This method ensures that different grass fibers have the same initial crack and applied deformation, allowing direct comparison of the degree of inhibition of crack opening by residual compressive stress in the cortex.
[0106] (5) Surface photo-oxidation test. Referring to the fluorescent ultraviolet lamp exposure principle of ISO 4892-3:2024, a UVA-340 lamp was used, with an irradiance of 0.76 W / (m²) at 340 nm. 2 The exposure time was 800 hours, consisting of 8 hours of UV irradiation at 60℃ and 4 hours of condensation at 50℃. After exposure, the surface area of the grass fibers was measured using attenuated total reflectance Fourier transform infrared spectroscopy (4000-650 cm⁻¹). -1 The resolution is 4cm. -1 A total of 32 scans were performed. At a depth of 1715cm... -1 The absorbance of the nearby carbonyl peak is similar to that at 1456 cm⁻¹. -1 The ratio of the absorbance of the characteristic peaks of polypropylene is used as the surface carbonyl index, with five locations tested in each group. This index is used to directly evaluate whether the weather-resistant components are concentrated to protect the fiber surface.
[0107] (6) Combined UV irradiation and mechanical abrasion test. Following the simultaneous exposure mode of ISO 19721:2022, each group of grass fibers was tufted into 300mm × 300mm artificial turf samples. All samples used the same polypropylene base fabric, with a stitch pitch of 3 / 8 inch, a longitudinal stitch count of 180 stitches / m, a grass height of 50mm, and a grass fiber surface weight of 1250g / m². 2 Filling density: 18.0 kg / m³ 2 Quartz sand with a particle size of 0.5-1.0 mm and 5.0 kg / m³ 2 Thermoplastic elastomer particles with a particle size of 0.8-1.5 mm.
[0108] The lawn sample was fixed on the surface of a rotating drum with a diameter of 500 mm, and a UVA-340 lamp was used to provide 0.76 W / (m²) at 340 nm. 2 Irradiance (nm) was maintained, blackboard temperature was controlled at 60±3℃, and water was sprayed for 15 minutes every 4 hours. A vertical load of 150N was applied by an abrasion wheel equipped with 12 conical thermoplastic polyurethane shoe nails, and the relative sliding speed between the abrasion wheel and the sample was 0.25m / s. The test lasted for 240 hours, with a total of 21,600 abrasion cycles.
[0109] After the test, 100 grass fibers were randomly selected from each sample, and the number of longitudinal forks with a length of not less than 2.0 mm was counted under a 20x stereomicroscope. Five lawns were tested in each group, and the average value was taken. In addition, 20 grass fibers were taken from the untreated sample and the combined exposed sample, and the breaking strength was tested according to the basic principles of GB / T 14344-2022 at a clamping distance of 100 mm and a tensile speed of 100 mm / min. The percentage of the average breaking strength after combined exposure to the average breaking strength before exposure was taken as the breaking strength retention rate.
[0110] Of the six types of tests mentioned above, melt tensile response, gel mass fraction, and aggregate D90 directly verify the effect of the timing of the addition of the stable-nucleation masterbatch on the core material; free thermal shrinkage, microcrack opening displacement, and warpage height directly verify the controlled shrinkage window and the core-skin stress balance; and surface carbonyl index, longitudinal branching number, and fracture strength retention rate verify the continuous synergy between the surface concentration of weather-resistant components and residual compressive stress under long-term photo-oxidation and mechanical wear conditions. There is a clear causal order among the various test indicators, rather than using a single conventional mechanical indicator to replace different contributing characteristics.
[0111] The F30 melt strength, strain hardening factor, gel mass fraction, and aggregate D90 in Table 1 are the average values of independent repeated tests. The relative standard deviation of F30 melt strength for each group is 2.1-3.8%, the relative standard deviation of strain hardening factor is 1.7-3.2%, the range of three parallel tests for gel mass fraction does not exceed 0.03 percentage points, and the statistical difference of aggregate D90 in different fields of view does not exceed 0.09 μm. The results in Tables 2 and 3 are the arithmetic mean of all valid samples in each group. Outliers were only removed after confirmation of sample clamp slippage, microscopic image defocusing, or equipment shutdown; data were not selectively deleted according to the results.
[0112] The melt tensile response, gel mass fraction, and nano-nucleating agent agglomeration size test results of the high-performance polypropylene used in Examples 1-3 and Comparative Example 1 are shown in Table 1. Examples 4, 5, Comparative Example 3, and Comparative Example 4 used the same high-performance polypropylene as Example 1, so the indicators in Table 1 are the same as those in Example 1.
[0113] Table 1. Branching and dispersion test results of high-performance polypropylene
[0114]
[0115] The microcrack opening displacement, warpage height, and surface carbonyl index of Examples 1-5 and Comparative Examples 1-4 are shown in Table 2.
[0116] Table 2. Results of tests on shrinkage morphology, microcrack opening, and surface photo-oxidation.
[0117]
[0118] The results of longitudinal forking number and fracture strength retention after combined ultraviolet irradiation and mechanical wear are shown in Table 3.
[0119] Table 3. Results of combined ultraviolet irradiation and mechanical wear tests
[0120]
[0121] As shown in Table 1, when the amount of multifunctional branching agent increased from 0.050 parts to 0.220 parts, the melt strength of F30 increased by 5.4 cN, the strain hardening factor increased by 0.47, while the gel mass fraction only increased by 0.10%. Further increasing the branching agent to 0.500 parts resulted in only a further increase of 1.9 cN in the melt strength and a strain hardening factor of only 0.09, but a 0.31% increase in the gel mass fraction. This change does not represent a linear relationship between the amount of branching agent and performance, but rather a nonlinear transition around 0.220 parts, from a dominance of effective long-chain linkages to a rapid increase in localized high branching and microgels.
[0122] As shown in Table 1, when 0.220 parts of JN851 were used in Example 1, the F30 melt strength was 16.8 cN, the strain hardening factor was 1.84, and the gel mass fraction was only 0.18%. While improving the tensile load-bearing capacity of the melt, no significant cross-linked gel was generated. In Example 2, after reducing JN851 to 0.050 parts (the lower end of the claim scope), the gel mass fraction decreased to 0.08%, but the F30 melt strength and strain hardening factor decreased to 11.4 cN and 1.37, respectively, indicating insufficient branched connections and a reduction in the recoverable orientation strain that the core layer could store.
[0123] In Example 3, increasing JN851 to 0.500 parts resulted in an increase in the F30 melt strength and strain hardening factor to 18.7 cN and 1.93, respectively. However, the gel mass fraction nonlinearly increased to 0.49%, approaching the 0.50% upper limit specified in this application. The aggregate D90 also increased from 0.46 μm in Example 1 to 0.54 μm. Although the melt strength of Example 3 was higher than that of Example 1, the initial breaking strength and post-exposure retention of the finished straw fibers did not continue to improve, indicating that higher dosage of multifunctional branching agents is not always better. When the dosage approaches the upper limit, localized hyperbranching or microgels become new sources of stress concentration.
[0124] Example 1 and Comparative Example 1 used the same total amounts of isotactic polypropylene, DCP, JN851, and stabilizing-nucleating masterbatch, differing only in the order of addition of the stabilizing-nucleating masterbatch. The F30 melt strength of Comparative Example 1 decreased from 16.8 cN to 8.6 cN, and the strain hardening factor decreased from 1.84 to 1.18, indicating that RIANOX 1010 and RIANOX 168 captured free radicals after entering the front-end reaction zone, significantly inhibiting long-chain branching. Simultaneously, the D90 of the nano-calcium carbonate agglomerates in Comparative Example 1 increased to 1.41 μm, approximately 3.1 times that of Example 1, indicating that the nano-nucleating agent underwent secondary agglomeration after complete branching reaction and front-end high-temperature shearing. These results demonstrate that "branching and devolatilization first, followed by the addition of the stabilizing-nucleating masterbatch" is not a simple adjustment of the feeding sequence, but rather a necessary sequence to simultaneously maintain free radical reaction efficiency and nano-dispersion.
[0125] In Table 2, Examples 4, 5, Comparative Examples 3, and 4 are arranged around the same set of skin free thermal shrinkage rates of 4.2% and core free thermal shrinkage rates of 8.6%. Examples 4 and 5 are located 0.5% inside the lower and upper boundaries of the effective window, respectively, while Comparative Examples 3 and 4 are located 0.5% outside the corresponding boundaries. This dense arrangement allows for comparison of performance changes before and after crossing the critical boundary when the shrinkage rate changes by only 1.0%, eliminating differences in raw materials, drawing temperature, drawing ratio, and cooling rate.
[0126] As shown in Table 2, the actual shrinkage rate of Example 1 is located in the middle between the free thermal shrinkage rates of the skin and core layers. Its microcrack opening displacement after 5000 bends is 8.6 μm, and the warpage height of the 200 mm sample is only 0.8 mm. Example 4 reduces the actual shrinkage rate to 4.7%, which, although still within the shrinkage window, is only 0.5% higher than the skin layer's free thermal shrinkage rate. The residual compressive stress in the skin layer is small, and the microcrack opening displacement increases to 15.2 μm. Example 5 increases the actual shrinkage rate to 8.1%, and the microcrack opening displacement decreases to 6.9 μm. However, since it is only 0.5% lower than the core layer's free thermal shrinkage rate, the remaining shrinkage margin in the core layer for balancing the compressive stress of the skin layer is small, and the warpage height increases to 2.5 mm. Therefore, a comprehensive balance exists within the shrinkage window, and Example 1 achieves a better match between crack closure and morphological stability.
[0127] Comparative Example 3 showed an actual shrinkage rate of 3.7%, only 0.5% lower than the skin's free thermal shrinkage rate. However, the microcrack opening displacement suddenly increased from 15.2 μm in Example 4 to 24.9 μm, while the warpage height did not increase significantly. This abrupt change indicates that when the actual shrinkage rate exceeds the lower limit of the skin's free thermal shrinkage rate, the skin no longer forms axial residual compressive stress, but is in a state of insufficient free shrinkage or residual tension, and the driving force for the opening of surface microcracks increases significantly.
[0128] Comparative Example 4 showed an actual shrinkage rate of 9.1%, only 0.5% higher than the free thermal shrinkage rate of the core layer, with a microcrack opening displacement of 6.2 μm. However, the warpage height increased abruptly from 2.5 mm in Example 5 to 8.4 mm. When the actual shrinkage rate exceeded the free thermal shrinkage rate of the core layer, both the skin and core layers were compressed to a state smaller than their respective free equilibrium lengths. The core layer could no longer balance the compressive stress of the skin layer with residual tensile stress, resulting in overall compressive instability of the straw fibers. This result demonstrates that a smaller microcrack opening cannot be used as the sole basis for a higher shrinkage rate; the shrinkage rate must simultaneously be lower than the free thermal shrinkage rate of the core layer.
[0129] The actual shrinkage rate of Comparative Example 1 was 6.3%, but its core free thermal shrinkage rate decreased to 5.5% due to suppressed branching. The actual shrinkage rate actually exceeded the core free thermal shrinkage rate, resulting in a warpage height of 5.1 mm. This result links the reaction sequence to the subsequent shrinkage stress formation: the early addition of the stabilizer not only reduces melt strength but also diminishes or even eliminates the core's ability to provide shrinkage driving force, causing the shrinkage rate originally set for Example 1 to fall outside the effective window.
[0130] Based on the core-sheath mass ratio of Example 1, the weather-resistant masterbatch in Example 1 accounts for 1.92% of the total grass fiber mass. However, this 1.92% of weather-resistant masterbatch is entirely located in the sheath layer, which accounts for 32.0% of the grass fiber mass, resulting in a weather-resistant masterbatch concentration of 6.00% within the sheath layer. In Comparative Example 2, after uniformly distributing the same total amount across the entire cross-section, the nominal weather-resistant masterbatch concentration in any surface area decreased to 1.92%, which is only 32.0% of the sheath layer concentration in Example 1. Therefore, Comparative Example 2 does not reduce the total amount of weather-resistant components, but rather eliminates their spatial enrichment in the service surface layer, directly verifying the effect of the cross-sectional spatial configuration.
[0131] Example 1 and Comparative Example 2 have the same total raw material composition, the same total stabilizer and weather-resistant component dosage, and the same stretching and shrinkage conditions. The only difference is that Example 1 uses a core-skin separation structure, while Comparative Example 2 uses a homogeneous monolayer structure. After 800 hours of UV exposure, the surface carbonyl index of Comparative Example 2 is 0.177, significantly higher than that of Example 1 (0.118), indicating that the effective concentration of the weather-resistant component on the surface of the straw fibers is reduced after dilution throughout the entire cross-section of the homogeneous material. The microcrack opening displacement of Comparative Example 2 is 18.6 μm, also significantly higher than that of Example 1, indicating that the homogeneous monolayer material cannot utilize two homogeneous polypropylene regions with different free thermal shrinkage rates to form stable surface residual compressive stress.
[0132] Comparative Example 3 and Example 1 have the same weathering system in their outer layer, with surface carbonyl indices of 0.119 and 0.118, respectively, which are essentially the same. However, the number of longitudinal forks in Comparative Example 3 is 29.4 per 100 cracks, approximately 6.1 times that of Example 1, and the fracture strength retention rate decreases from 86.8% to 58.9%. This indicates that while the weathering component can reduce surface photo-oxidation, it cannot replace the suppression of crack opening by residual compressive stress in the outer layer. Conversely, although Comparative Example 2 uses the same total amount of weathering component, its carbonyl index and number of forks are both increased because the weathering component is not concentrated in the outer layer. The above results respectively verify the independent effects of surface weathering protection and crack closure, and demonstrate that the two form a continuous synergistic effect in Example 1.
[0133] The combined exposure test simultaneously applied UVA irradiation, periodic water spraying, a 60°C thermal environment, and shoe spike abrasion. UVA and moisture promoted photo-oxidation and molecular chain breakage on the polypropylene surface, while shoe spike contact subjected the already formed surface defects to repeated bending, shearing, and localized tensile stress. Since all turf samples used the same base fabric, tuft density, grass height, and infill system, the differences in the number of forks and the retention rate of breaking strength in Table 3 mainly stemmed from the weather resistance system, core-sheath structure, and residual stress state of the grass fibers themselves.
[0134] As shown in Table 3, after 240 hours of combined UV irradiation and 21,600 mechanical abrasion cycles, Example 1 had the best overall result with 4.8 longitudinal forks per 100 roots and a fracture strength retention rate of 86.8%. Example 2, due to insufficient branching agent dosage, had inadequate core melt strength and recoverable orientation strain, resulting in an increased fork number of 9.7 per 100 roots. Although Example 3 had higher melt strength, it was close to the upper limit of gelation, with a fork number of 8.1 per 100 roots, which was not superior to Example 1. The data showed a non-linear variation with a near-optimal overall value around 0.220 parts.
[0135] Example 4 is located inside the lower boundary of the retraction window, with relatively small skin compressive stress and a number of forks of 12.4 per 100, and a fracture strength retention rate of 76.4%. Example 5 is located inside the upper boundary, with strong crack closure ability and a number of forks of 6.3 per 100, but the increased warping causes uneven local mechanical wear, and the fracture strength retention rate is 83.9%, which is still lower than that of Example 1.
[0136] Although the microcrack opening displacement in Comparative Example 4 was as low as 6.2 μm, the number of forks after combined exposure reached 19.7 per 100 fibers, with a fracture strength retention rate of only 66.6%. This was not due to insufficient residual compressive stress in the surface layer, but rather because the actual shrinkage rate exceeded the free thermal shrinkage rate of the core layer, resulting in overall warping and compressive instability, with the raised grass fibers experiencing more concentrated abrasion from the cleats. This result further indicates that this application selected a shrinkage window where the compressive stress in the skin layer and the tensile stress in the core layer were balanced, rather than simply pursuing the maximum compression.
[0137] Further comparison of Example 1, Comparative Example 2, and Comparative Example 3 reveals the two effects. In Comparative Example 2, after eliminating the core-skin separation, the surface carbonyl index increased from 0.118 to 0.177, indicating that the photo-oxidation reaction was significantly accelerated when the weather-resistant components were not enriched on the surface; its microcrack opening displacement also increased to 18.6 μm, indicating that a homogeneous cross-section could not fix the residual compressive stress on the surface. Comparative Example 3 retained the skin-weather-resistant system of Example 1, with its carbonyl index remaining at 0.119, but because the actual shrinkage rate was lower than the skin's free thermal shrinkage rate, the microcrack opening displacement increased to 24.9 μm. The two comparative examples led to an increase in the number of forks through two pathways: "accelerated oxidation" and "easier crack opening," respectively.
[0138] The low carbonyl index, small microcrack opening displacement, and low warpage height of Example 1 indicate that the weather-resistant components are enriched, and the compressive stress in the cortex and the tensile stress in the core are simultaneously effective. The weather-resistant system first reduces the number of chain breaks and microcracks formed per unit exposure time; when defects still form, the residual compressive stress in the cortex reduces its opening displacement; the residual tensile stress in the core and the centrosymmetric cross-section limit the overall compressive buckling of the straw fibers. These three factors work in sequence to reduce the number of crack initiation, crack propagation rate, and local wear concentration after combined exposure.
[0139] The data in this application also show that reaching an extreme value for a single indicator does not equate to optimal overall performance. Example 3 exhibits the highest F30 melt strength, but gelation is close to the upper limit; Examples 5 and Comparative Example 4 show smaller microcrack opening displacements, but warpage gradually increases; Comparative Example 2 has the same total amount of stabilizer and weathering agent as Example 1, but the effective concentration in the surface layer is insufficient. Example 1 does not pursue maximum values for each individual indicator, but rather achieves a combination of parameters that simultaneously hold true for melt branching, gelation control, surface weathering resistance, crack closure, and morphological stability.
[0140] Based on Tables 1-3, the technical effects of this application stem from three consecutive contributing features. The sequential separation of front-end free radical branching, vacuum devolatilization, and downstream stabilization-nucleation allows the core polypropylene layer to achieve melt tensile bearing capacity and recoverable orientation strain under controlled gel mass fraction, while simultaneously inhibiting secondary agglomeration of nanonucleating agents. The spatial separation of the homogeneous polypropylene skin and core allows the linear, highly oriented skin layer to concentrate on weather resistance and surface bearing capacity, while the branched core layer undertakes shrinkage drive and flexural support. The actual shrinkage rate lies between the free thermal shrinkage rates of the skin and core layers, and rapid cooling under low tension fixes the residual compressive stress in the skin layer and the residual tensile stress in the core layer.
[0141] The three characteristics mentioned above correspond to reaction efficiency, cross-sectional functional configuration, and crack driving force control, respectively, and cannot be replaced by the addition of a single antioxidant, single branching treatment, or ordinary heat setting. The weather-resistant system delays the initiation of microcracks, reduces crack opening due to residual compressive stress in the cortex, and maintains the overall morphological stability of the grass fibers in the core layer, ultimately reducing longitudinal bifurcation, fibrillation, and breakage during long-term outdoor service.
[0142] In continuous production, the front-end branching reaction zone, vacuum devolatilization zone, and downstream feeding zone can be arranged sequentially along the same reactive extrusion equipment, eliminating the need for a second complete melt granulation of the stabilized-nucleation masterbatch. Core-sheath co-extrusion, main drawing, supplementary drawing, controlled shrinkage, and cooling and shaping can be completed sequentially on the continuous straw production line. The actual shrinkage rate can be controlled by a closed-loop system of linear speeds at the inlet and outlet guide rollers of the shrinkage zone, while the free heat shrinkage rate can be re-measured after changing raw material batches or adjusting the drawing heat history to adjust the speed difference in the shrinkage zone accordingly.
[0143] When the cross-section of the grass fibers is adjusted from a flat shape to an elliptical, rhomboid, or longitudinally reinforcing shape, the core layer remains symmetrically arranged around the geometric center of the cross-section, and the offset of the geometric center of the core layer relative to the geometric center of the grass fiber cross-section remains within 5% of the equivalent radius. Conventional changes to the width, thickness, or height of the grass fibers do not alter the three technical conditions: reaction sequence, functional space separation, and retraction window. Therefore, the process of this application can be integrated with existing continuous extrusion and tufting processes for artificial grass fibers.
[0144] In this invention, high-performance polypropylene, obtained through a sequence of front-end branching, vacuum devolatilization, and downstream stabilization-nucleation, is used as the core layer raw material. Isotactic polypropylene containing weather-resistant masterbatch and not subjected to free radical branching is used as the skin layer raw material. The controlled shrinkage rate is determined based on the free heat shrinkage rate measured under the same stretching heat history. Weather-resistant artificial turf fibers are obtained through centrosymmetric core-skin co-extrusion, main stretching, supplementary stretching, controlled shrinkage, and low-tension cooling. The resulting grass fibers can be manufactured into artificial turf using conventional tufting, backing, and filling processes.
[0145] The technical solution has been described above based on embodiments of the present invention. Those skilled in the art can adjust the specific raw material grade, straw cross-sectional profile, production line dimensions, and continuous operation speed without departing from the technical concept of the present invention. The scope of protection of the present invention should be determined by the technical solution as defined in the claims.
Claims
1. A method for preparing high-performance polypropylene, characterized in that, Includes the following steps: S1. Based on 100 parts by weight of isotactic polypropylene, mix 0.01-0.08 parts by weight of free radical initiator and 0.05-0.50 parts by weight of multifunctional branching agent to obtain the reactant. S2. The reactants are melted and reacted at 180-220°C for 30-120 seconds to form sparse long-chain branched polypropylene. S3. Vacuum devolatilization for 15-60 seconds at a gauge pressure of -0.06 to -0.095 MPa; S4. Add 0.5-3.0 parts by weight of stabilizing-nucleating masterbatch to the melt after vacuum devouring. The stabilizing-nucleating masterbatch contains processing antioxidant, auxiliary antioxidant and surface-treated nano-nucleating agent. S5, mix, extrude and granulate to obtain high-performance polypropylene.
2. The weather-resistant artificial turf fiber based on high-performance polypropylene and its preparation process according to claim 1, characterized in that: The free radical initiator is one of dicumyl peroxide, 2,5-dimethyl-2,5-di-tert-butylperoxyhexane or benzoyl peroxide. The multifunctional branching agent is one of trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, or triallyl isocyanurate.
3. The weather-resistant artificial turf fiber based on high-performance polypropylene and its preparation process according to claim 1, characterized in that: The isotactic polypropylene has a melt flow rate of 2.0-8.0 g / 10 min at 230℃ and 2.16 kg, and an isotactic index of not less than 96.0%.
4. The weather-resistant artificial turf fiber based on high-performance polypropylene and its preparation process according to claim 1, characterized in that: The stabilized nucleating masterbatch comprises, by mass percentage, 70-88% polypropylene carrier, 4-10% processing antioxidant, 4-10% auxiliary antioxidant, and 4-12% surface-treated nano-nucleating agent, with the sum of the contents of each component being 100%. The D50 particle size of the nano-nucleating agent is 30-100 nm.
5. A high-performance polypropylene prepared by any one of claims 1-4.
6. A preparation process for weather-resistant artificial turf fiber based on high-performance polypropylene, characterized in that, Includes the following steps: S1. Using the high-performance polypropylene described in claim 5 as the core layer material, and using isotactic polypropylene and weather-resistant masterbatch that have not undergone free radical branching treatment and have a gel mass fraction of no more than 0.10% as the skin layer material. S2. Prepare single-layer standard samples from the core layer raw material and the skin layer raw material at the same main drawing temperature, main drawing ratio, supplementary drawing temperature and supplementary drawing ratio as the composite grass fiber, and determine the free heat shrinkage rate at 115-145℃. S3. Co-extrude the core layer material and the sheath layer material into a composite primary grass fiber with the sheath layer continuously covering the core layer. S4. Perform main stretching and supplementary stretching on the composite primary grass fibers in sequence; S5. Implement controlled shrinkage at 115-145℃, so that the actual shrinkage rate is greater than the free thermal shrinkage rate of the skin material and less than the free thermal shrinkage rate of the core material. S6. Under constant length or tension of 0.02-0.12 cN / dtex, cool to below 40°C within 2-8 seconds.
7. The preparation process of weather-resistant artificial turf fiber based on high-performance polypropylene according to claim 6, characterized in that: The core layer accounts for 55-80% of the total mass of the composite primary grass fibers, and the sheath layer accounts for 20-45%. The offset of the geometric center of the core layer cross section relative to the geometric center of the composite primary grass fiber cross section is no greater than 5% of the equivalent radius of the composite primary grass fibers.
8. The preparation process of weather-resistant artificial turf fiber based on high-performance polypropylene according to claim 6, characterized in that: The weather-resistant masterbatch comprises, by mass percentage, 45-65% polypropylene carrier, 4-10% primary antioxidant, 4-10% secondary antioxidant, 10-20% hindered amine light stabilizer, 4-10% ultraviolet absorber, and 10-25% pigment, with the sum of the contents of each component being 100%. The mass fraction of the weather-resistant masterbatch in the skin layer raw material is 3-8%.
9. The preparation process of weather-resistant artificial turf fiber based on high-performance polypropylene according to claim 6, characterized in that: The temperature of the main stretching is 70-105℃ and the stretching ratio is 3.2-4.8 times, while the temperature of the supplementary stretching is 115-145℃ and the stretching ratio is 1.05-1.25 times.
10. The preparation process of weather-resistant artificial turf fiber based on high-performance polypropylene according to claim 6, characterized in that: The difference in free thermal shrinkage rates between the core material and the skin material is 2.0%-7.0%. The actual shrinkage rate is 0.5%-4.0% higher than that of the skin material and 0.5%-4.0% lower than that of the core material.